Proceedings of the International Rice Genetics Symposium, 27-31 May 1985 (Manila, Philippines, 1986)
The book continues updating knowledge of genetics of the rice plant and the precise identification of the nature of the genetic control of important economic characters have become particularly urgent in the context of recent advances in molecular biology and genetic enginneering.
Keywords: Rice,Lúa; Genetics,Nhân giống